NEW METHOD OF PRODUCTION OF ALUNINUM SILICON ALLOYS - V. K. Afanasiev; E. L. Marukovich; M. N. Churik; V. V. Gertsen; A. V. Gorshenin; V. A. Samon (Литьë и металлургия)
A new approach to the preparation of aluminum-silicon alloys, based on the concept of the leading role of hydrogen in determining the structure and properties of alloys consists in using as charge materials of silicon dioxide (silica) and hydrogen instead of crystalline silicon was described. Practical ways to implement the new method were proposed on the example of industrial alloys prepared on charge synthetic alloy. It is shown that the application of the proposed method allows to improve the mechanical properties and reduce the coefficient of thermal expansion alloys, Al-Si. The effect of heat treatment on mechanical properties, density and thermal expansion of synthetic alloys was researched.